Factors influencing English learning from different backgrounds of departments at a vocational school in Surakarta - Anissa, Dewi; Susiati, Susiati (Universitas Islam Malang, 2025)
The era of globalization that is increasingly rapid requires someone to have English language skills, especially in vocational education where language skills have a direct impact on students' work abilities. Although many studies have explored motivation in learning English, few have specifically examined differences across departments. This study identifies factors influencing English learning motivation among 11th-grade students from various departments with a total of 208 participants from accounting, marketing, visual communication design, and office management at a vocational school in Surakarta, Indonesia. This quantitative study employed stratified random sampling; this study used a structured questionnaire based on the motivation strategy for learning (MSLQ). Data analysis used descriptive statistics, one-way ANOVA, and the Kruskal-Wallis test. The results of the study showed statistically significant variations in English learning motivation across all majors, with a P-value of 0.000 from the accounting department showing the highest motivation with an average of 4.24 and the marketing department showing the lowest average of 3.68. These findings indicate that career relevance, learning environment, teaching methods, and intrinsic and extrinsic motivation can significantly influence students' English learning attitudes. This research contributes to understanding the complex dynamics of motivation in vocational education and provides insights for developing targeted English language education strategies that are in line with student's professional aspirations.